The effect of government internal auditors’ moral reasoning and situational pressure on the tendency to commit fraud when auditing: An experimental study - Novita Puspasari; Meutia Karunia Dewi (Journal of Economics, Business, and Accountancy Ventura, 2015)
This study aims to examine the effect of government internal auditors’ moral levels and situational pressures on the tendency to commit fraud when conducting audit. Based on the hypothesis, despite the situational pressures, the government internal auditors who have a high moral level will not commit fraud at the time of auditing. Meanwhile, the government internal auditors who have a low moral level will com-mit fraud at the time of auditing when there is situational pressure. To test the hypothesis, a 2×2 factorial experiment is conducted involving 68 students of STAR-BPKP of Jenderal Soedirman University. The results indicate that the government internal auditors who have a high moral level will not commit fraud in the time of auditing despite some situational pressures. Meanwhile, the government internal auditors who have a low moral level will commit fraud at the time of auditing either there is a situational pressure or not. The implications of this study are to streng-then the supervisory system for the internal auditors at the time of auditing, to provide protection for whistle- blowers who report the presence of fraud committed by auditors, and to be consistent in giving reward to professional auditors and pu-nishment to auditors who are convicted of fraud at the time of auditing.